Evaluation of oxygen therapy in adult patients in teaching hospital of Sergipe - Bianca L. SANTOS; Maria L. BARROS; Gessica U. OLIVEIRA; Daniela T. OLIVEIRA; Lucimara M. ANDRADE; Simony M. SOARES; Geovanna C. CARDOSO; Milena M. XAVIER; Marcell C. SILVA; Fábio J. AMORIM (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objective: To evaluate oxygen therapy prescriptions for patients under clinical care admitted to a teaching hospital in Sergipe. Methods: This is a cross-sectional, descriptive, retrospective and quantitative study, in which the medical records and prescriptions of 28 patients using oxygen (O2) hospitalized between March and June 2021 were evaluated. to the indication of O2 and initial oxygen saturation (SatO2), and the prescriptions regarding the inclusion of O2 in the prescription, target saturation, O2 delivery device and initial flow or initial inspired O2 concentration. After data collection, a panel of experts was formed, composed of a pulmonologist, physical therapists and pharmacists to evaluate the findings and suggest interventions to be carried out. Results: Of the patients evaluated, 89.3% had an indication for oxygen therapy, but 72.4% of the medical records did not present information on initial SatO2. Of the sample analyzed, 53.6% did not have prescribed O2, 75.0% did not have a SatO2 target, 42.9% did not have an O2 delivery device, and 67.9% did not have the initial flow or inspired concentration of oxygen. initial O2. In addition, the nasal catheter was the most prescribed device (85.2%). The panel of experts suggested nine interventions to be carried out, which ranged from training professionals involved in the entire process of using medical oxygen, to modifying the current medical prescription model to meet the necessary requirements for a prescription of adequate oxygen, in order to promote the practice of rational use of oxygen and adjustments in the work process. Conclusion: The study showed that most of the items evaluated in the oxygen prescriptions presented non-compliance with international recommendations. These findings justify carrying out interventions with the care team.